2021
DOI: 10.3390/ph14030254
|View full text |Cite
|
Sign up to set email alerts
|

Tioconazole and Chloroquine Act Synergistically to Combat Doxorubicin-Induced Toxicity via Inactivation of PI3K/AKT/mTOR Signaling Mediated ROS-Dependent Apoptosis and Autophagic Flux Inhibition in MCF-7 Breast Cancer Cells

Abstract: Cancer is a complex devastating disease with enormous treatment challenges, including chemo- and radiotherapeutic resistance. Combination therapy demonstrated a promising strategy to target hard-to-treat cancers and sensitize cancer cells to conventional anti-cancer drugs such as doxorubicin. This study aimed to establish molecular profiling and therapeutic efficacy assessment of chloroquine and/or tioconazole (TIC) combination with doxorubicin (DOX) as anew combination model in MCF-7 breast cancer. The drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 113 publications
1
17
0
Order By: Relevance
“…These results indicate that QRKSG protects renal tubular cells against ADR-induced renal damage. The findings are consistent with previous research ( Lieberthal and Levine, 2009 ; Kaushal et al, 2020 ; Zhou et al, 2020 ; Bhosale et al, 2021 ; El-Gowily et al, 2021 ), and the relevant target graphs are shown in Supplementary Figure S3 . Therefore, QRKSG could promote autophagy and anti-apoptosis through the expression of AKT1, CASP3, BCL2L1, and mTOR, thereby conferring protection to the podocytes and maintaining renal function and tubular homeostasis.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that QRKSG protects renal tubular cells against ADR-induced renal damage. The findings are consistent with previous research ( Lieberthal and Levine, 2009 ; Kaushal et al, 2020 ; Zhou et al, 2020 ; Bhosale et al, 2021 ; El-Gowily et al, 2021 ), and the relevant target graphs are shown in Supplementary Figure S3 . Therefore, QRKSG could promote autophagy and anti-apoptosis through the expression of AKT1, CASP3, BCL2L1, and mTOR, thereby conferring protection to the podocytes and maintaining renal function and tubular homeostasis.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that the levels of RNA and protein expression of ATG5 increased in Pg-LPS induced HGFs [ 40 ]. El-Gowily have confirmed that up-regulation of Beclin-1 could produce disruptive autophagy [ 41 ]. Pg-LPS significantly increased the proteins levels of ATG5, Beclin1, and p-NF-κB p65/NF-κB p65 in HGFs, and the ratio of LC3-II/LC3-I was increased in dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the level of RNA and protein expression of ATG5 is increased in HGF stimulated by LPS [39] . El-Gowily have con rmed that up regulation of Beclin-1 could produce disruptive autophagy [40] . Our research is consistent with the above description.…”
Section: Discussionmentioning
confidence: 99%